2014
DOI: 10.1590/s0100-06832014000100005
|View full text |Cite
|
Sign up to set email alerts
|

Soil quality indicators in a rhodic kandiudult under different uses in northern Parana, Brazil

Abstract: SUMMARYSustainable use of soil, maintaining or improving its quality, is one of the goals of diversification in farmlands. From this point of view, bioindicators associated with C, N and P cycling can be used in assessments of land-use effects on soil quality. The aim of this study was to investigate chemical, microbiological and biochemical properties of soil associated with C, N and P under different land uses in a farm property with diversified activity in northern Parana, Brazil. Seven areas under differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
9
0
3
Order By: Relevance
“…O uso de diferentes doses de dejetos líquidos de suínos e o preparo do solo também influenciaram a atividade enzimática do solo, que apresentou diferentes tendências de acordo com a enzima (celulase, arilsufatase e fosfatase ácida), as diferentes doses de dejetos utilizadas e o manejo e a profundidade do solo estudada, de modo que a atividade das enzimas do solo foi considerada uma medida sensível capaz de detectar mudanças no solo em razão da aplicação de dejetos de suínos (Balota et al, 2011). A urease também demonstrou ser uma das enzimas mais sensíveis na análise de indicadores de qualidade do solo no Paraná, promovendo os mais distintos níveis entre diferentes usos do solo (Kuwano et al, 2014).…”
Section: Resultsunclassified
“…O uso de diferentes doses de dejetos líquidos de suínos e o preparo do solo também influenciaram a atividade enzimática do solo, que apresentou diferentes tendências de acordo com a enzima (celulase, arilsufatase e fosfatase ácida), as diferentes doses de dejetos utilizadas e o manejo e a profundidade do solo estudada, de modo que a atividade das enzimas do solo foi considerada uma medida sensível capaz de detectar mudanças no solo em razão da aplicação de dejetos de suínos (Balota et al, 2011). A urease também demonstrou ser uma das enzimas mais sensíveis na análise de indicadores de qualidade do solo no Paraná, promovendo os mais distintos níveis entre diferentes usos do solo (Kuwano et al, 2014).…”
Section: Resultsunclassified
“…Kuwano et al (2014), working with soils under different uses in Northern Paraná, observed that the sugarcane areas under the burning system presented the highest qCO 2 , probably as a result of the burning before harvest, which decreases soil carbon inputs; moreover, the disturbance of the soil through heavy tillage on the renovation of the sugarcane plantation disrupts the microbial community not only by the breakdown of soil aggregates, but also by the loss of water from the soil.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, an ecosystem out of balance will present high values of qCO 2 and low values of qMIC, which indicates greater energy consumption and higher level of stress of the biomass (Anderson and Domsch, 1990;Evangelista et al, 2013;Kuwano et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the activities of dehydrogenase and cellulase were associated to fodder radish cropping, and in a lesser extent, to the multicropping of cover crops, as observed in the PCA analysis (Figure 2). The treatment with wheat also decreased the L-C in 2009, as a possible result of a stimulus to the microbial activity mediated by root exudation during vegetative growth, followed by deposition of residues more resistant to degradation on the soil after harvest, with larger C/N ratio, which makes more difficult the humification and formation of L-C. Lower concentrations of L-C in the soil cropped with fodder radish and wheat are in agreement with lower soil respiration, because microbial communities use more easily the more labile C fractions as substrate for growth and maintenance (BINI et al, 2013;BLAIR et al, 1995;KUWANO et al, 2014).…”
Section: Resultsmentioning
confidence: 97%
“…The soil microbial biomass works as transitory reservoir of nutrients originated from mineralization of SOM or fertilizers (CARDOSO et al, 2013), reducing losses like phosphate fixation and nitrate leaching (FAGOTTI et al, 2012;FRANK;GROFFMAN, 2009;RANGEL;. Considering that the speed of decomposition of plant residues rely on its chemical composition, mainly the C to N ratio and lignin content, the type of residue also affect the microbial activity and biomass (BINI et al, 2013;KUWANO et al, 2014).…”
Section: Introductionmentioning
confidence: 99%